A Tool for the Sustainable Management of Urban Conservation Units amid Climate Change - Silva, Guilherme Henrique Pereira da; Branchi, Bruna Angela (Scientific Journal ANAP, 2025)
Objective – To propose an instrument for the sustainable management of urban Conservation Units (UCs), based on integrated monitoring of environmental, social, economic, and governance dimensions, as a strategy for climate change adaptation. Methodology – This research adopts a descriptive and exploratory approach, combining qualitative and quantitative methods. Techniques included document analysis, field visits, and an online questionnaire used to assign weights to 15 indicators distributed across four dimensions. The data were integrated into a composite index and applied in a simulated manner to two UCs in the city of Campinas (São Paulo, Brazil). Originality/Relevance – The study addresses a gap in the literature regarding assessment tools specifically designed for urban UCs focused on sustainability and climate adaptation. It stands for proposing an integrated tool suitable for urban contexts and aligned with the principles of Nature-based Solutions (NbS). Results – The developed index enabled the classification and comparison of the performance of two UCs in Campinas, revealing the relative weaknesses of the ARIE Mata de Santa Genebra compared to the APA of Campinas, particularly in the social and economic dimensions. Theoretical/Methodological Contributions – The main methodological contribution is the development of a composite sustainability index for urban protected areas, combining indicators validated by diverse stakeholders and grounded in internationally recognized criteria, such as the Bellagio STAMP and the IUCN Global Standard for NbS. Social and Environmental Contributions – The proposed instrument can support public managers in decision-making processes, promoting more effective management of urban green areas. Furthermore, it encourages the adaptive use of UCs as a strategy to mitigate urban vulnerabilities and enhance socio-environmental resilience.